HUDUD KELANTAN DAN PENGISLAHANNYA - Deris, Mohd Noor (Jurnal Syariah, 2019)
The article reviews the importallce of the 1993 Hudud Bill of Kelantall. In the author's view, the Bill has invited many criticism from the Federal Governmellt as well as academician. The aspect criticised are justice of the Bill, qualification of drafters and lack of provisions. The author gives several suggestions on how to improve the Bill including how to implement Syariah Law wisely.